2010
DOI: 10.1007/s11433-010-0151-9
|View full text |Cite
|
Sign up to set email alerts
|

Ni-based Ni-Fe-B-Si-Ta bulk metallic glasses

Abstract: The glass-forming ability and properties of Ni-based Ni-Fe-B-Si-Ta bulk metallic glasses are explored in this work. The alloy compositions are determined by using a combination of the cluster line approach, the multi-alloying strategy and the substitutions of similar elements. Bulk metallic glasses with diameters of 3 mm take shape at compositions formulated under the cluster-plus-glue-atom model [M 9 B]B~[(Ni 1−x Fe x ) 7.71 (Si 0.66 Ta 0.34 ) 1.29 B]B 0.94 =(Ni 1−x Fe x ) 70.5 B 17.7 Si 7.8 Ta 4 , x=0.35-0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…From the aspect of microstructure, a novel cluster-related model named cluster-glue-atom model has been proposed by Chuang Dong [21][22][23][24]. This method showed great success in understanding and designing good glass-formers in Fe-based, Ni-based and rare-earth-based and Zr-based systems, etc [13,25,26]. Under the guidance of this cluster-glue-atom model, glass-formers were treated as isolated clusters plus glue atoms.…”
Section: Introductionmentioning
confidence: 99%
“…From the aspect of microstructure, a novel cluster-related model named cluster-glue-atom model has been proposed by Chuang Dong [21][22][23][24]. This method showed great success in understanding and designing good glass-formers in Fe-based, Ni-based and rare-earth-based and Zr-based systems, etc [13,25,26]. Under the guidance of this cluster-glue-atom model, glass-formers were treated as isolated clusters plus glue atoms.…”
Section: Introductionmentioning
confidence: 99%
“…bulk metallic glasses, glass forming ability, thermal stability, elastic properties Citation: Minor alloying addition or microalloying technology has proven to be an effective approach in promoting glass formation, enhancing thermal stability and improving the plasticity of BMGs [20][21][22]. It has been found that microalloying with proper alloying elements can dramatically improve the GFA of various BMGs [23][24][25]. Previous studies showed that the GFA of Cu-, Mg-and ZrCu-based bulk metallic glasses were significantly enhanced by adding Ag [26][27][28][29].…”
mentioning
confidence: 99%
“…It has been found that microalloying with proper alloying elements can dramatically improve the GFA of various BMGs [23][24][25]. Previous studies showed that the GFA of Cu-, Mg-and ZrCu-based bulk metallic glasses were significantly enhanced by adding Ag [26][27][28][29].…”
mentioning
confidence: 99%
“…In this study, we aimed to develop an FePBNb metallic glass system with a much higher GFA and good soft-magnetic properties by examining the effect of Ni addition on the GFA and the soft-magnetic properties based on two factors: (1) As a ferromagnetic element, Ni has been shown to be effective in improving the soft-magnetic properties in permalloys and FeNi-base metallic glasses [5,8,9]. (2) Ni shows mutual solubility with Fe and has been shown to be effective in improving the thermal stability of the supercooled liquid as well as allowing the alloy to approach a eutectic point composition leading to a high GFA [10][11][12].…”
mentioning
confidence: 99%